Membaca Pandangan Filosof Gianni Vattimo dalam Pendidikan Agama Kristen di Indonesia - Yanwar Valentino; Nina Jesika; Ribka Filistina; Akelince Doo (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
Common problem in the world of education, especially Christian Religious Education is when assuming the teacher's hermeneutic is the only final truth regardless of the responses—whether positive or negative—from students. In fact, Gianni Vattimo's view in the context of education in the author's mind assumes that the suppression of ideas, restrictions on creativity in Christian Religious Education, and the critical power of students is inevitable, and indeed seems to have to exist. The response to this event becomes important as a hermeneutic of the teacher as a Christian Education facilitator to see the extent to which the response becomes meaningful. This paper uses qualitative research with literature search techniques, namely through recent books and journals related to Christian Education and the philosophy of Gianni Vattimo. The results of this study indicate that the grand narrative in Christian Education, after going through Vattimo's view (pensiero débole), has been at the intersection as a response, participation and appreciation of the truth that is plural / plural. Both in the church and school environment as a space for Christian Education existence. In addition, the author finds that the relationship of faith in Christian Religious Education is translated into praxis so that it is useful, empowering as well as a manifestation of God's inherent love with others as an abundance of God's love or as a community of faith/belief that is in harmony.